Effect of focal adhesion kinase inhibition on osteoblastic cells grown on titanium with different topographies - Helena Bacha LOPES; Alann Thaffarell Portilho SOUZA; Gileade Pereira FREITAS; Carlos Nelson ELIAS; Adalberto Luiz ROSA; Marcio Mateus BELOTI (University of São Paulo, 2020)
Abstract Objective The present study aimed to investigate the participation of focal adhesion kinases (FAK) in interactions between osteoblastic cells and titanium (Ti) surfaces with three different topographies, namely, untreated (US), microstructured (MS), and nanostructured (NS). Methodology Osteoblasts harvested from the calvarial bones of 3-day-old rats were cultured on US, MS and NS discs in the presence of PF-573228 (FAK inhibitor) to evaluate osteoblastic differentiation. After 24 h, we evaluated osteoblast morphology and vinculin expression, and on day 10, the following parameters: gene expression of osteoblastic markers and integrin signaling components, FAK protein expression and alkaline phosphatase (ALP) activity. A smooth surface, porosities at the microscale level, and nanocavities were observed in US, MS, and NS, respectively. Results FAK inhibition decreased the number of filopodia in cells grown on US and MS compared with that in NS. FAK inhibition decreased the gene expression of Alp, bone sialoprotein, osteocalcin, and ALP activity in cells grown on all evaluated surfaces. FAK inhibition did not affect the gene expression of Fak, integrin alpha 1 ( Itga1 ) and integrin beta 1 ( Itgb1 ) in cells grown on MS, increased the gene expression of Fak in cells grown on NS, and increased the gene expression of Itga1 and Itgb1 in cells grown on US and NS. Moreover, FAK protein expression decreased in cells cultured on US but increased in cells cultured on MS and NS after FAK inhibition; no difference in the expression of vinculin was observed among cells grown on all surfaces. Conclusions Our data demonstrate the relevance of FAK in the interactions between osteoblastic cells and Ti surfaces regardless of surface topography. Nanotopography positively regulated FAK expression and integrin signaling pathway components during osteoblast differentiation. In this context, the development of Ti surfaces with the ability to upregulate FAK activity could positively impact the process of implant osseointegration.